Analysis and Testing of Power Swing Function of Numerical Distance Relay - Le, Kim Hung; Vu, Phan Huan (Old Journal, 2018)
Avoiding mistake trip of the mechanical distance relay during power swing, the power swing function implementation in numerical distance relays are used to overcome this drawback. Now, the relay has to discriminate between the fault and the power swing conditions. It uses dual-quadrilateral characteristics that are based on the measurement of the time it takes the positive-sequence impedance to cross the two blinders. The main purpose of the function is block the power swing or trip on the out-of-step. This paper presents power swing function theory and explains setting values of SEL vendors. Also, the paper performs to test effectively power swing function on the relay protection SEL421 by Distance function in TU3.0 softwave of Omicron CMC256 device. In addition, we describe a 220KV power system model, explain how to analyze swing with Matlab/Simulink software. Thereby results show that benefits this function can yield of high reliability, fast time response.